Impact of the Coronavirus Disease Pandemic and Related Vaccination in an Orthopedic Clinic in the United Arab Emirates: An Observational Study - Kim, Seung-Kook; Park, Seo-jung; Cho, Dae-won; Kwak, Hong-suk; Jin, Hee-yon; Eum, Su-hyun; Heo, Eun-jung; Kim, Gi-eun; Ji, Ha-young; Park, Seung-jun (Frontiers in Surgery, 2022)
The coronavirus disease (COVID-19) pandemic has influenced hospital visiting patterns. Although vaccination has decreased infection rates and disease severity, hospital visiting patterns and associated treatment changes related to orthopedics remain unexplored in the Middle East. Therefore, this study aimed to examine the impact of the COVID-19 pandemic and vaccination on individual departments dealing with musculoskeletal disorders in the United Arab Emirates. Relationships between publicly available national data on the number of COVID-19 polymerase chain reaction tests and confirmed and recovered cases during May 2020 – July 2021 and hospital data on the number of outpatients, inpatients, operations, and physiotherapy consultations were analyzed. In January 2021, the relationship between vaccination rate and orthopedic unit utilization was evaluated after vaccination campaign initiation. Multifactorial analysis revealed that an increased number of COVID-19-related deaths correlated with a decreased number of joint operations. Negative linear relationships were observed among confirmed and death cases with inpatient treatment and joint operation as well as recovered cases with inpatient treatment. Recovered cases with inpatient treatment and joint operation showed a positive linear relationship. Inpatient spine treatment showed a positive relationship with vaccination rates. The COVID-19 pandemic influenced orthopedic treatment in the Middle East, and vaccination campaigns facilitated inpatient spine treatment.